Understanding Illicit Drug Use Trends During the Carnival Holiday in the Brazilian Capital Through Wastewater Analysis - Sodré, Fernando Fabriz; Freire, Diogo de Jesus Soares; Alcântara, Daniel Barbosa; Maldaner, Adriano Otávio (Frontiers in Analytical Science, 2022)
Cocaine and cannabis consumption during and after the 2019 Carnival holiday were assessed using the wastewater-based epidemiology (WBE) in the capital of Brazil, Brasília. The substances 11-nor-9-carboxy-Δ9-tetrahydrocannabinol (THC-COOH), cocaine (COC), benzoylecgonine (BE), and cocaethylene (COE) were monitored in composite samples (24h) collected in the entrance of North-Wing (NW) and South-Wing (SW) wastewater treatment plants (WWTP) for 15 consecutive days, including the Carnival holiday. Aliquots (100 mL) were enriched with isotope-labeled standards, solid-phase extracted and analyzed by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Results reveal higher cocaine consumption during the Carnival (average of 2.8 ± 0.7 g/1000inh/day) compared to the subsequent period (average of 1.7 ± 0.3 g/1000inh/day). Cannabis (THC) use was also higher during the holiday (14 ± 5 g/1000inh/day) but differences were not significative (unpaired t-test, 95%) compared to the following days (11 ± 3 g/1000inh/day), where consumption remained relatively constant corroborating that cannabis overall consumption is less affected by occasional abuse. Regarding cocaine, an unusual low consumption was noticed in the weekend immediately after the Carnival Holiday, indicating lower demand or supply issues. Higher cocaine and cannabis use was observed throughout the entire sampling period in the area covered by NW-WWTP, probably due to the higher proportion of young people. This investigation brings the first data on cannabis use in Brazil by WBE and confirms this strategy as a well consolidate tool for estimating illicit drug use and abuse.